The Republic of Uganda : Country Integrated Fiduciary Assessment 2004, Volume 5. Local Government Integrated Fiduciary Assessment - World Bank (Washington, DC, 2013)
The Uganda Country Integrated Fiduciary Assessment (CIFA) consolidates (in five volumes) the results, and recommendations of various diagnostic processes, including the Public Expenditure Review (PER), the Country Financial Accountability Assessment (CFAA), the Country Procurement Assessment report (CPAR), the Tracking Poverty, Reducing Spending Assessment, and the Local Government Integrated Fiduciary Assessment (LGIFA). This integrated approach is designed to address comprehensively the budgetary, financial accountability, and transparency challenges that Uganda is facing. CIFA marks a first step toward adopting a single standard assessment of Uganda's public financial management (PFM) systems for all levels of government. The report provides the Government of Uganda (GoU), its development partners (DPs), and other stakeholders with a candid review of the public sector challenges, and an assessment of the key fiduciary risks, and opportunities for corrupt practices. Fiduciary risk is defined as the risk that expenditure is not properly accounted for, that it is not used for its intended purposes, and that it does not represent value for money (VFM). The assessment shows that in the last four years the GoU has made significant progress in strengthening, and updating the legal framework, and regulatory environment for PFM, thus reducing the risk associated with a lack of clear rules and regulations. In addition, the GoU has reduced the fiduciary risks associated with poor budget formulation, and preparation through the PER process. The quality of information provided in the annual accounts also has improved. Notwithstanding, there remains high fiduciary risk, associated with: the enforcement of procurement, and payroll rules and procedures; the incompleteness of data on debt and contingent liabilities; weak independent oversight; and, the timeliness and effectiveness of legislative and public scrutiny. The Local Government Integrated Fiduciary Assessment (LGIFA) highlights the considerable progress made over the last decade in providing services at the local level; from this base, however, it notes with concern that the budgeting and planning processes at LGs are poor at articulating specific local needs within overall national objectives, and policies. The assessment also raises concerns over the ability, desire, and willingness of local residents, and politicians to hold their administrations to account for their performance.